Distributed and reliable decision-making for cloud-enabled mobile service platforms - Joongheon Kim; Aziz Mohaisen (International Journal of Distributed Sensor Networks)
This article proposes distributed decision-making algorithms for reliable operation in cloud-assisted social network architectures. The considered architecture consists of three types of units: a cloud platform, access units, and mobile units (MUs). For reliable operations in such architectures, two distributed decision-making algorithms are proposed: (1) decision-making for fair connection at MUs and (2) decision-making for dynamic buffering at access units . For the decision-making in fair connection at MUs, the deployed MUs find their new access units to be associated with them when currently associated access units are out of order. The proposed algorithm works considering buffer backlog in access units, achievable rates with access units, and the number of associated MUs in access units. For the decision-making in dynamic buffering at access units, the buffers in access units are dynamically controlled for time-average expected power consumption minimization (i.e. energy-efficiency maximization) subjected to buffer stability.